A New Fractional Model for Cancer Therapy with M1 Oncolytic Virus. (7th June 2021) - El Younoussi, Majda; Hajhouji, Zakaria; Hattaf, Khalid; Yousfi, Noura
Abstract : The aim of this work is to propose and analyze a new mathematical model formulated by fractional differential equations (FDEs) that describes the dynamics of oncolytic M1 virotherapy. The well-posedness of the proposed model is proved through existence, uniqueness, nonnegativity, and boundedness of solutions. Furthermore, we study all equilibrium points and conditions needed for their existence. We also analyze the global stability of these equilibrium points and investigate their instability conditions. Finally, we state some numerical simulations in order to exemplify our theoretical results.